Cost-effectiveness analysis of direct oral anticoagulants versus low-molecular-weight heparin and no thromboprophylaxis in primary prevention of cancer-associated venous thromboembolism in China - Yue Wu; Yue Wu; TianChen Yin; TianChen Yin; GuiLin Jian; GuiLin Jian; Tao Wan; Tao Wan; Tao Wan; Benhong Zhou; Benhong Zhou (Frontiers Media S.A., 2024)
Background and objectiveCancer-associated venous thromboembolism (CAVTE) is a preventable, life-threatening complication with a considerable morbidity and mortality. Primary venous thromboembolism (VTE) prophylaxis is currently recommended; however, the health and economic benefits have not been evaluated and compared in China. This study aimed to assess and compare the cost-effectiveness of anticoagulants in primary CAVTE prevention among cancer patients in China.MethodsA Markov model with a 5-year horizon was established to evaluate the costs and effectiveness of direct oral anticoagulants (DOACs) compared to low-molecular-weight heparins (LMWHs) and no prevention in primary prophylaxis of CAVTE in China. Key clinical outcomes were obtained from the available clinical trials, comparing DOACs (rivaroxaban and apixaban) with LMWHs or with no thromboprophylaxis. Utility and the cost inputs were all obtained from the published literature or local data with public sources. The total costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratios (ICERs) were estimated as the main endpoints of the modal for each strategy. The assessment of uncertainty was performed involving deterministic sensitivity analysis and probabilistic sensitivity analysis (PSA). Impact of time horizon, generic drug price, and individual DOACs were assessed in scenario and subgroup analyses.ResultsPrimary prophylaxis using DOACs were projected to yield 1.866 QALYs at a cost of $3,287.893, resulting in the ICERs of $12,895.851 (DOACs vs. no-thromboprophylaxis) and $43,613.184/QALYs (LMWHs vs. DOACs). Sensitivity analysis revealed that ICER was sensitive to the VTE and bleeding risk, drug cost of anticoagulants, self-payment ratio, and overall death rate of cancer. Probabilistic sensitivity analysis showed that DOACs and LMWHs had a 48% and 45% probability of being cost-effective at a 5-year time horizon, respectively. When the time horizon extended to 10 years, DOACs achieved a cost-effective probability of 43%. Among individual DOACs, apixaban was found to be the preferred strategy in VTE prevention due to its incremental health gain with an acceptable cost increase.ConclusionPrimary thromboprophylaxis with DOACs was cost-effective in cancer patients at a willing-to-pay (WTP) threshold of $37,125.24/QALY in China. Cancer death rate, risk of VTE and major bleeding, and the drug cost assumed greater relevance and importance in the decision-making process for primary thromboprophylaxis in cancer.